(untitled) (International Seven Journal of Multidisciplinary, 2023)
This study analyzed how small and medium-sized enterprises influence urban and educational development in Brazilian municipalities, considering economic, social, and structural transformations observed in recent decades. The research was conducted as a qualitative literature review, with the selection of national scientific articles and technical reports published between 2010 and 2023. The results show that the growth of small and medium-sized enterprises increases the tax base, promotes job creation, and demands integrated public policies, creating a more structured urban environment with higher quality educational services. It was evident that municipalities investing in interaction between the productive sector and the educational sector achieve higher human development indexes, better territorial distribution of economic activities, and greater capacity to attract investments and retain qualified professionals. It is concluded that strengthening these enterprises and integrating urban and educational planning form a virtuous cycle of sustainable growth.